The executive regulations of the consumer protection law = اللائحة التنفيذية لقانون حماية المستهلك - egypt (2025)
1 general obligations -- 2 provision of certain contracts -- 3 remote contracting -- b consumer protection agency -- organization of complaints submission -- judicial officer capacity -- dispute examination and certification